Colors Systems and their effects on textile Designs - Azza Halwany (Journal of Architecture, Art & Humanistic Science, 2020)
With the great development in computer programs, and the development of color theories using numerical calculation methods that give ease in determining the degree of color and reach it easily.There are some digital color theories that follow in many industrial fields such as (paint colors - colors of computers - televisions TV - mobile phone ...........)Thus, in order to obtain woven fabrics of a certain color, it is necessary to consider and define the set of previous variables, and to find a correlation between these factors to obtain the desired color degree.In the case of upholsters fabrics with different motifs like (upholstery fabrics - curtain fabrics - floor mats - ground and fabrics), we find that to express the color space in the design, it requires defining all the above mentioned variables, and the most important of these variables is the type The textile composition used to obtain this color space, as it is understood that each color space in the textile design has its own textile structure.In order to obtain a successful textile design that is competitive in the internal and external markets, the textile designer needs to be familiar with the color theories trained in determining the colors to deal with the distribution within the design space, as well as a good knowledge of the different types of textile structures that can be used on the color area chromatically required in textile design.Using different color yarns for both warp and weft, to show how obtain the desired color effects according to the kind of textile structure, with installations of all other variables (warp yarn number - weft yarn number - warp density in the unit of measurement - the density of the weft in the unit of measurement - the material of the warp - the material of the weft .....) that affected on the final shape of the textile design.Color appearance in weaving design requires good knowledge of the textile designer with the changing factors in woven fabrics, and the extent of the impact of these factors on the quality of the product design, the quality of the appearance of woven fabric in accordance with studied scientific theories, the ability of the designer to link between the woven textile design, and how to choose colors according to a scientific theory The best performance of the textile product.